Identifikasi Lactobacillus sp pada Orangutan Sumatera (Pongo abelii) Liar Menggunakan KIT API 50 CHL di Stasiun Penelitian Suaq Belimbing Aceh Selatan - Wardinal Wardinal; Safika Safika; Yulia Sari Ismail (Universitas Islam Negeri Ar-Raniry, 2019)
Lactic Acid Bacteria (LAB) has many benefits for human and animal health and has been widely used as a probiotic. One of the LAB is the genus Lactobacillus which consists of many species used for fermentation and food preservation. This study was conducted to isolate and identify the LAB of the genus Lactobacillus from the faeces of wild Sumatran Orangutan (Pongo abelii) at the Suaq Belimbing Research Station in South Aceh. Bacterial isolation was carried out using Man Rogosa Sharpe Agar (MRSA). Colonies that grew on MRSA media were observed for morphology and were Gram stained. Biochemical tests were conducted using KIT API 50 CHL. Data analysis used the Apiweb computer program Version V-5.2. The results showed that the OUL isolate was a species of Lactobacillus delbrueckii ssp delbrueckii, with an identity of 93.8%. Based on this, it can be concluded that there is a Lactic Acid Bacteria of the Lactobacillus in the faeces of wild Sumatran Orangutan (Pongo abelii) at the Suaq Belimbing Research Station in South Aceh.